Comida que vem da terra - Hortêncio, Claudomiro Braga; Carvalho, Elza Dias de Oliveira; Lima, Keila de Oliveira; Botassim, Rosa Maria Ferreira (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf